The Effect of Transformational Leadership, Organizational Culture, and Work Motivation on Job Satisfaction and Employee Performance at PT Amerta Travelindo Sentosa in Surabaya, East Java - Shabana, Muhammad Ainul (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study aims to analyze the influence of Transformational Leadership, organizational culture, and Work Motivation on Job Satisfaction and Employee Performance at PT. Amerta Travelindo Sentosa Surabaya. This research is quantitative one using data sourced from questionnaires measured with a Likert scale. The sample used a saturated sampling technique, including all employees, totaling 75 individuals. The collected data was then analyzed to test the research hypotheses using structural equation modeling techniques with the Smart-PLS program. The results showed that Transformational Leadership, organizational culture, and Work Motivation each have a significant effect on Job Satisfaction. Similarly, Job Satisfaction has a direct and significant effect on Employee Performance. Transformational Leadership, organizational culture, and Work Motivation do not have a direct significant effect on Employee Performance, but data analysis indicates that these three independent variables can significantly influence Employee Performance through the mediation role of Job Satisfaction. This means that the management of Transformational Leadership, organizational culture, and Work Motivation must be able to foster Job Satisfaction to ultimately have a significant impact on Employee Performance.